Advancing gender research from the nineteenth to the twenty-first centuries - Segal, Marcia Texler, 1940-; Demos, Vasilikie P. (Bingley, UK : Emerald JAI, 2008)
Volume 12 consists of fourteen original essays by multi-national and multi-disciplinary scholars. Four discuss and analyze the 19th Century writings of Harriet Martineau (British author), considered to be early examples of sociology and gender studies. A range of Martineau's writings are explored including her critical review of the Salem witch hunts and her letters to a young Irishman. Several essays focus on gendered implications of the state, for example, the European Union or the Eastern European Bloc. A third set focus on gender and social institutions and some investigate family-related issues including power relations regarding race, childbearing, the impact of religious fundamentalism, issues related to aging, health and medicine, and sport. Some are based on presentations given at the International Sociological Association Congress in Durban, South Africa in July, 2006. Others are drawn from the Martineau Society Working Seminar at National University of Ireland at Maynooth in May, 2007. Continuing in the tradition established by the "Advances in Gender Research" series, it explores gender as a social institution and social construct. The essays complement one another in their topic examination, issues and themes, adding nuance to contemporary Gender Studies.
Introduction: advancing gender research from the nineteenth to the twenty-first centuries / Marcia Texler Segal, Vasilikie Demos -- Witch hunts and enlightenment: Harriet Martineau's critical reflections on Salem / Susan Hoecker-Drysdale -- Harriet Martineau's Irish romance: the lady oracle and the young repealer / Deborah A. Logan -- Harriet Martineau and the sociology of health: England and her soldiers / Mary Jo Deegan -- Harriet Martineau: the forerunner of cultural studies / Anna Dryjanska -- Some things are not negotiable: gender, sovereignty, and Poland's integration into the European Union / Alexandra Gerber -- Breaking their way in: women jockeys at the racetrack in Brazil / Miriam Adelman, Fernanda Azeredo Moraes -- Exercising social power: the case of marriage / Kathryn A. Sweeney -- Evangelicals, invested individualism and gender / Sally K. Gallagher -- Fundamentalist feminists spar with the patriarchy: interpretive strategies of Israeli rabbinic court pleaders / Susan Weiss -- Surviving widowhood: gender and race effects on health-related coping strategies / Tariqah A. Nuriddin, Carolyn C. Perrucci -- Re-examining the meanings of childbirth: beyond gender and the "natural" versus "medical" dichotomy / Sarah Jane Brubaker, Heather E. Dillaway -- Redefining "reproductive rights": an ecofeminist perspective on in vitro fertilization, egg markets and surrogate motherhood / Laura Corradi -- How advertising for psychotropics constructs an enhanced gendered self / Elianne Riska, Thomas Heikell.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Gender identity -- History -- 19th century; Gender identity -- History -- 20th century; Gender identity -- History -- 21st century; Sex role -- History -- 19th century; Sex role -- History -- 20th century; Sex role -- History -- 21st century; Gender studies, gender groups; Social Science -- Gender studies